A Study on Structural Parameters of Solid Potassium Salt Mines - Zhang, Yukun (International Journal of Natural Resources and Environmental Studies, 2026)
To ensure the safety and efficiency of solid potassium salt mine mining, this paper focuses on the research of stope structural parameters, including stope room span, roof safety thickness, and stope layout form. Based on the equilibrium arch theory and simply supported beam theory, the limit span of the stope room is analyzed and calculated, and the reasonable room span is determined by combining mining technology and safety requirements. Using the elastic mechanics thin plate theory and H. Tresca yield criterion, the safety thickness of the stope roof is calculated to ensure the overall stability of the stope during mining. Two stope layout schemes (uniform layout of rooms and pillars, interval large pillars with equal-width rooms) are designed, and the parameters of each scheme are calculated and compared from the aspects of pillar safety factor and recovery rate. The research results show that the reasonable room span of the carnallite ore layer is 8m, the safe thickness of the roof isolation layer should be more than 7.5m, and the interval large pillar layout scheme has higher recovery rate while ensuring safety, which can provide a theoretical basis and engineering reference for the design and construction of solid potassium salt mines.